EFFECT OF PHYTOESTROGENS IN COWPEA (Vigna unguiculata) ON BREAST CANCER IN MENOPAUSE - Hermawan Wibisono; Nina Rini Suprobo (STIKes Kepanjen, 2022)
Perimenopausal or early postmenopausal women can be prescribed Hormone Replacement Therapy to help them manage moderate to severe menopausal symptoms. One of the primary concerns is that Hormone Replacement Therapy may escalate breast cancer risk. Natural polyphenols' anticancer properties are now a popular issue in many research labs over the last two decades. Polyphenols may be useful in the development of anticancer drugs. Cowpea (Vigna unguiculata) contains a high concentration of flavonoids, phenolic compounds, and antioxidants. Phytoestrogens can bind to mammalian ER and act as inadequate aromatase inhibitors, that might lower the breast cancer risk through limiting circulating estrogen levels.